Dairy cow traits responses in dependency of breed and environmental characteristics along a rural-urban gradient - Pinto Garcia, Ana; Justus Liebig University Giessen (My University, 2021)
Rising megacities represent the highest state of urbanization, which is an important ongoing transition process in the socio-ecological field. The dairy livestock in India is based in rural and (peri-)urban smallholders, a vital livestock sector in a society that strongly relies on milk and milk products as protein sources in vegetarian diets. The social-ecological heterogeneity along rural-urban gradients in rising megacities might influence the dairy production, through phenotypic trait expressions. However, the impact of social-ecological factors along an urbanizing environment in dairy cattle had not yet been evaluated in terms of phenotypic trait expressions.This thesis focused on the study of phenotypic trait expressions including production traits, body condition, methane emissions, cow wellbeing indicators and health traits to study the effects of urbanization on dairy production. In this regard, the rising megacity of Bangalore, in southern India, was selected for its challenging environmental conditions and social complexity. Mixed modelling approaches were applied considering both social and ecological continuous descriptors simultaneously to investigate the impact of social-ecological components on production and functional traits. A rural-urban gradient, based on an index- based approach comprising build-up density and distance to the city center, was considered as a novel environmental descriptor. Possible genotype by environment (G×E) interaction are studied, considering different cattle breeds and the level of urbanization as an environmental descriptor.
Keywords: ddc:630